THE DIRECTION OF HUMAN RESOURCE MANAGEMENT - Azizova Sitora Shodiqulovna (Journal Park Publishing, 2023)
Human resource management has come a long way from being a traditional administrative function to a strategic partner that contributes to the success of an organization. The evolution of HRM(Human resource management) has been shaped by changes in the business environment, technology, and the changing needs and expectations of employees. One of the latest trends in HRM is the focus on employee well-being, which has gained prominence due to the COVID-19 pandemic. This article explores the direction of HRM towards employee well-being, its impact on organizations, and the challenges that come with it.
Keywords: Human Resource Management, Employee Well-being, COVID-19, Organizational Success.